Heat and Hypoxia Exposure Mediates Circadian Rhythms Response via Methylation Modification in Apostichopus japonicas - Wu, Jiong; Zhang, Weiwei; Li, Chenghua (Frontiers in Marine Science, 2021)
As global warming progresses, heat and hypoxia are gradually becoming important factors threatening the survival, reproduction, and development of marine organisms. To determine the effect of heat and hypoxia on Apostichopus japonicus, whole genome methylation of the respiratory tree was determined under heat, hypoxia, and heat-hypoxia conditions [designed as heat stress treatment (HT), hypoxia treatment (LO), and heat-hypoxia combined treatment (HL) groups]. The number of differentially methylated regions (DMRs) under three treatments was determined based on the Venn diagram. The network of the DMRs associated with promoters that were co-existed under the three conditions showed that circadian rhythm was involved based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Circadian rhythm-related genes, CRY1a, CRY1b, CLC, and TIM, decreased in LO and HL groups, while CRY1a, CRY1b, and BMAL1 increased in the HT group. Bisulfite sequencing PCR (BSP) showed that the methylation levels of CpG island regions in the promoters of CRY1a and CRY1b were upregulated in HT, LO, and HL groups, leading to the decreased promoter activity of CRY1a and CRY1b. RNAi of CRY1a and CRY1b led to increased enzyme activities of two energy-related enzymes, pyruvate kinase (PK) catalyzing the rate-limiting step in glycolysis, and ATPase hydrolyzing ATP to ADP, which were also increased under the three tested conditions. Thus, it was concluded that A. japonicus may respond to the heat, hypoxia, and heat-hypoxia stresses via the DNA methylation of heat, hypoxia, and heat-hypoxia stresses via the DNA methylation of CpG islands of circadian rhythm-related genes, which increased the activity of energy-related enzymes.